The relation between nurse burnout and turnover intention: the moderator effect of perceived organizational support and distributive justice in tertiary firsr-class Hospital in China - Peijin , Zhao (2017)
In recent years, Chinese population is aging and growing rapidly, and the healthcare industry has been facing a problem of nurse shortage and high turnover rate. To get a better understand of the factors which may influence turnover intention in China, an integrated analysis was designed. The main goals of this research are twofold: to comprehend whether burnout is related to turnover intentions, and if so how perceived organizational support and distributive justice may influence the relationship between burnout and nurse’s turnover intention. To answer these questions, a survey was done in eight tertiary first-class hospitals in China. 266 returned validity questionnaire were contributing to this study. The results show that both personal burnout and work related burnout are positively related to nurse’s turnover intention. Perceived organizational support moderates the effect of nurse’s personal burnout on turnover intention and distributive justice moderates the effect of nurse’s work related burnout on turnover intention in China.